The Shadow of Sabotage: Unraveling the Insecurity Threats Impacting Oil Operations in Ondo and Delta States of Nigeria - Akindoyo, Olorunsemi Akin (Kashere Journal of Politics and International Relations, 2025)
Niger Delta, home to Nigeria’s vast petroleum wealth, remains mired in a complex security crisis that undermines economic productivity and deters foreign direct investment (FDI). This study interrogates the insecurity threats—particularly sabotage, oil theft, militant violence, and kidnapping—affecting oil operations in Ondo and Delta States between 2017 and 2022. Drawing upon the State Capacity Theory, the study employs a mixed-methods approach comprising survey questionnaires (n = 200), in-depth interviews, and secondary data analysis. Findings reveal a high incidence of oil theft (mean score = 4.65), kidnapping (mean = 4.63), and violence against oil workers (mean = 4.15), all significantly linked to diminished FDI inflows. While the Nigerian government has implemented legal reforms such as the Petroleum Industry Act (2021), weak enforcement and systemic governance failures persist, especially in managing local grievances and protecting oil infrastructure. Regression analysis, although indicating a weak statistical link between insecurity and oil output (p = 0.507), corroborates the perception that insecurity contributes to operational disruptions, revenue losses, and investor apathy. The study recommends a multi-dimensional intervention strategy, encompassing community inclusion, security sector reform, and infrastructural development, to address insecurity and stabilize investment conditions in Nigeria’s oil heartland.